Gambaran Faktor Penyebab Kejadian Tuberkulosis (TB) Paru di Wilayah Kerja Puskesmas Tenateke Sumba Barat Daya Tahun 2025 - Klemens Nikander Dapa Ghuda; Yendris K. Syamruth; Sigit Purnawan; Imelda F.E. Manurung (Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium Tuberculosis, this bacteria usually attacks the lungs, but TB bacteria can also attack any part of the body such as the spine and brain. This study aims to describe the causes of pulmonary TB such as ventilation, floor type, temperature, humidity, residential density, contact history, ownership and location of livestock pens, and smoking habits. This type of research is descriptive research, namely a research method carried out with the main objective of creating a more objective picture of a situation with a cross-sectional approach. The sample in this study was selected using total sampling with a total sample of 34 pulmonary TB sufferers. Data were collected through interviews using questionnaires and observations of the physical condition of the sample houses and analysis was carried out univariately. The results showed that ventilation, floor type, temperature, humidity, contact history, ownership and location of livestock pens had a percentage above fifty percent that met health requirements, while for residential density and smoking habits had a percentage above fifty percent that did not meet health requirements. This study concluded that ventilation, floor type, temperature, humidity, contact history, ownership and location of livestock pens were in the good category, while residential density and smoking habits were in the bad category.